2020
DOI: 10.1039/d0nj02993a
|View full text |Cite
|
Sign up to set email alerts
|

High-rate sodium insertion/extraction into silicon oxycarbide-reduced graphene oxide

Abstract: Silicone oxycarbide (SiOC) is gaining attention as a potential anode material for lithium-ion batteries due to its higher reversible capacity and high-rate capability. However, the employment of SiOC in sodium-ion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Due to the enlargement of interspace and improved electronic conductivity as well as mechanical property, the hierarchical nitrogen-doped MoS 2 /SiOC composite achieved a facile reversible cycle of Na ions during the operation of the battery, namely 540.7 mAh/g of reversible capacity and almost 100% of capacity retention, also including excellent rate capability at 10 A/g. Putra et al [507] studied SiOC-graphene composites pyrolyzed from silicone oil and demonstrated their excellent performance. They also studied the effect of fluorinated ethylene carbonate in the electrolyte on the electrochemical performance.…”
Section: Anode Materials In Sodium-ion Batteriesmentioning
confidence: 99%
“…Due to the enlargement of interspace and improved electronic conductivity as well as mechanical property, the hierarchical nitrogen-doped MoS 2 /SiOC composite achieved a facile reversible cycle of Na ions during the operation of the battery, namely 540.7 mAh/g of reversible capacity and almost 100% of capacity retention, also including excellent rate capability at 10 A/g. Putra et al [507] studied SiOC-graphene composites pyrolyzed from silicone oil and demonstrated their excellent performance. They also studied the effect of fluorinated ethylene carbonate in the electrolyte on the electrochemical performance.…”
Section: Anode Materials In Sodium-ion Batteriesmentioning
confidence: 99%
“…[24][25][26] The O 1s spectrum was divided into four peaks located at 530.5, 531.6, 533.0, and 533.0 eV (Figure 2C), corresponding to the COOH bond, C─OH bond, C═O/O─Si bond, and Si─O─Si bond, respectively. [27,28] The presence of oxygen can not only enhance the wettability to reduce the inert surface area, but also serve as electrochemical active sites. [22,29] As shown in Figure 2D, the Si 2p spectrum can be deconvoluted into SiO 2 C 2 (101.8 eV), SiO 3 C (102.7 eV) and SiO 4 (103.5 eV), respectively, [28,30] suggesting that the Si could be coupled with carbon matrix through oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…[27,28] The presence of oxygen can not only enhance the wettability to reduce the inert surface area, but also serve as electrochemical active sites. [22,29] As shown in Figure 2D, the Si 2p spectrum can be deconvoluted into SiO 2 C 2 (101.8 eV), SiO 3 C (102.7 eV) and SiO 4 (103.5 eV), respectively, [28,30] suggesting that the Si could be coupled with carbon matrix through oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the low value of CE is attributed to the SEI layer formation. 40 The second, third, and fourth cycles exhibited significantly improved CE values of 95%, 96%, and 99.8%, respectively. The discharge and charge profiles of the S:MoP-5 electrode show sloping behavior which reveals the capacitive storage of sodium.…”
Section: Sodium-ion Batterymentioning
confidence: 87%